Scribal practices and the social construction of knowledge in antiquity, late antiquity and the Medieval Islam - Wissa, Myriam.; Brock, Sebastian P.; Vernus, Pascal. (Orientalia Lovaniensia analecta ;, 2017)
"Scribal practices across disciplines are often explored through divisions between words, stiches and verses, sections, scribal hands and marks, correction and copying procedures. This volume offers a different perspective: writing as shown here is, at its heart, a deeply social practice connecting narrative to the different categories of knowledge (linguistic, political, administrative, legal, historical and geographic) and literacy. The twelve essays investigate how scribal practices are related to the construction of knowledge and challenge the conventional boundaries. They address various types of knowledge whose potential is triggered by certain needs and values in the context of Antiquity, Late Antiquity and Medieval Islam from al-Andalus through Egypt, Syria to Iraq, Anatolia and Bactria as far afield as Ethiopia. The vast majority of the papers are related thematically and the overall connection between the articles is the salient feature of this volume. The papers also demonstrate how the local context has shaped scribal practices allowing for cross-cultural comparison."-- Publisher's website.